ABRASION WAVE OBSTRUCTS TOURISM DEVELOPMENT IN COASTAL REGIONS OF BINUANGEUN, LEBAK - BANTEN - Delyuzar Ilahude; Udaya Kamiludin (Marine Geological Institute of Indonesia, 2011)
Geographically, the study area is located in the southern coast of Java and also exposed to the influence of wave energy from the southeast, south and southwest. The energy flux of waves generated by surface wind components that affect the coastline and the surrounding waters of Binuangeun. The impact of the wave coming from southeast direction caused a continuous abrasion process in Binuangeun coast and its adjacent areas, included the tourism area in the eastern part of Binuangeun coast towards the center of the study area. The current movement along the coast was accompanied by sediments deposition which tends to westward. The value of sediments supply (Vq) in sample area point number 9 was bigger than the sample area number 4 about 33.703 m3/year within the same direction tendency of sediments deposition. Western part of Binuangeun coastal area would presumably become the sediment accumulation point throughout the year, while the erosion process in the central part of the study area were expanding and occured seasonally. Keywords : abrasion, Binuangeun, flux energy Secara geografis daerah penelitian terletak di pesisir selatan Pulau Jawa dan termasuk pantai terbuka terhadap pengaruh energi gelombang dari arah tenggara, selatan dan barat daya. Energi fluks gelombang yang dibangkitkan oleh komponen angin permukaan berpengaruh terhadap garis pantai perairan Binuangen dan sekitarnya. Efek gelombang dari arah tenggara mengakibatkan proses abrasi di pantai Binuangen dan sekitarnya, terutama kawasan wisata bagian timur pantai Binuangen hingga ke bagian tengah. Pergerakan arus sepanjang pantainya disertai oleh pengendapan sedimen yang cenderung mengarah ke barat. Nilai pasokan sedimen (Vq) pada titik tinjau 9 lebih besar dari pada di titik 4 yaitu sebesar 33.703 m3/tahun dengan pasokan sedimen cenderung bergerak ke arah barat. Daerah pesisir kawasan bagian barat Binuangen diperkirakan akan menjadi zona akumulasi sedimen sepanjang tahun, sementara proses erosi di bagian tengah daerah penelitian tetap berkembang dan berlangsung secara musiman. Kata kunci : abrasi, Binuangen, energi fluks